ANSWER
(3,1)
Step-by-step explanation
The given system of equations are
![y + 2 = x...(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3ffr7qpgonz9j753km6xpmrdoczmczge49.png)
and
![y = 2x - 5...(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7966koj1cooysywuzhuwb3cbcrc5knit9z.png)
Substitute the first equation into the second equation.
This implies that,
![y = 2(y + 2) - 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qar07nc1oo934eo1hawba0joxxwzhho8li.png)
Expand using the distributive property,
![y = 2y + 4 - 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sa8zqn0awpjp21s54g2ett53nm79j6zotu.png)
Group similar terms,
![y - 2y = 4 - 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mmnjbn9kmvp3n02poao88749mvk0w6jv1h.png)
![- y = - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kezprpmv7wp3i8oqzkozitwxg52t05as9g.png)
Multiply both sides by -1.
![y = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jg5mtcrg8fuyzryb57dtzqneu3tdvytnjt.png)
Put y=1 into equation (1).
![1 + 2 = x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y8fsjp8sxvzr5ehh52tcfxdsp7mopkor6o.png)
![x = 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/gn0ewdpib9ooyfthsjwp8oi4900vxj88n6.png)
The solution is (3,1)
The correct choice is B.